A Compilation of the Messages and Papers of the Presidents. Volume 8, part 1: James A. Garfield - Richardson, James D. (James Daniel), 1843-1914 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Compilation of the Messages and Papers of the Presidents. Volume 8, part 1" compiled by James D. Richardson is a historical collection first copyrighted in 1897. This volume preserves the proclamations, messages, and speeches of Presidents James A. Garfield, Chester A. Arthur, and Grover Cleveland during the 1880s. Part of an eleven-volume series spanning 1787 to 1902, it documents pivotal presidential communications during America's Gilded Age. The compilation itself sparked a political controversy over copyrighting public documents, leading to landmark prohibitions on federal government copyright claims. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Compilation_of_the_Messages_and_Papers_of_the_Presidents
Release date is 2004-05-01
Produced by Juliet Sutherland, Shawn Cruze and the Online Distributed Proofreading Team
Keywords: United States -- Politics and government; United States -- History -- Sources; Garfield, James A. (James Abram), 1831-1881; Presidents -- United States